2002
DOI: 10.1046/j.1528-1157.2002.45401.x
|View full text |Cite
|
Sign up to set email alerts
|

Gabapentin versus Lamotrigine Monotherapy: A Double‐blind Comparison in Newly Diagnosed Epilepsy

Abstract: Summary:Purpose: This randomised, double-blind study compared the newer antiepileptic drugs (AEDs) gabapentin (GBP) and lamotrigine (LTG) as monotherapy in newly diagnosed epilepsy.Methods: Patients with partial seizures with and/or without secondary generalization or primary generalized tonic-clonic seizures were randomized to either GBP or LTG. During 2-and 6-week titration periods, respectively, GBP dosage reached 1,800 mg/day, and LTG, 150 mg/day. In the subsequent 24-week maintenance phase, the dose could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
59
0
4

Year Published

2003
2003
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(64 citation statements)
references
References 21 publications
1
59
0
4
Order By: Relevance
“…Two studies have compared LTG and GBP and found little difference. 78,80 They were too short, however, to allow meaningful comparison of efficacy outcomes, so that the treatment failure outcomes reported in the studies were dominated by the drugs' similar and good tolerability.…”
Section: Arm Amentioning
confidence: 99%
“…Two studies have compared LTG and GBP and found little difference. 78,80 They were too short, however, to allow meaningful comparison of efficacy outcomes, so that the treatment failure outcomes reported in the studies were dominated by the drugs' similar and good tolerability.…”
Section: Arm Amentioning
confidence: 99%
“…This is particularly pertinent if more patients are lost from one treatment group than the other. 64 The majority of studies (93) accounted for all patients and six did not. 43,[65][66][67][68][69] Twelve studies, including eight abstracts, 40,41,[44][45][46][47]59,60 provided insufficient information.…”
mentioning
confidence: 99%
“…The majority of AEDs available have demonstrated a similar effi cacy for treating this type of crisis (Mattson et al 1985(Mattson et al , 1992Brodie et al 1999Brodie et al , 2002. Therefore, the choice of drug will fundamentally depend upon its pharmacokinetic profi le and the likelihood of causing secondary effects (Sánchez-Alvarez et al 2005) which, as we have seen, have particular repercussions among the elderly.…”
Section: First Choice Aeds For the Elderlymentioning
confidence: 94%